EFEKTIFITAS PEMBUATAN SERTIFIKAT TANAH WAKAF DI KUA OMBEN KABUPATEN SAMPANG-MADURA - jamiliya susantin; Ramalatika Ramalatika (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2021)
The implementation of waqf that occurs in the omben subdistrict is still done by religious law or on the basis of mutual trust, so that until now there are still many waqf land that does not have a certificate, which at some point could be the waqf land is sued by the heirs of the waqf (Wakif) and stated that the land belongs to him and whenever the waqf land can be taken by the heirs because the land is still in his personal name. Therefore, in order for thewakafan not to cause problems in the future, the Office of Religious Affairs (KUA) has an active role in handling the issue of the waqf as the Waqf Pledge Deed Official (PPAIW). In this study the author used a field research approach, where researchers must jump directly into the field involved with the local community. Data collection in the field that aims to explain the certification of waqf land in Omben Sampang Subdistrict. The results of this study stated that the role of KUA Omben in the creation of waqf land certificates only helps the community so that the waqf land can have legal force so that there is no dispute in it, by making a Deed of Waqf Pledge (AIW) which will be continued by making waqf land certificates submitted to the land office and assisting the administrative process only. And the efforts made by kua Omben to realize the importance of waqf land certificate is considered ineffective to see from the number of waqf land that still does not have a waqf land certificate. Although all efforts have been made but the community still does not register its waqf land to the Office of Religious Affairs (KUA) Omben as the Office of the Maker of Waqf Pledge Deed (PPAIW).